2017
DOI: 10.1080/15376516.2017.1313345
|View full text |Cite
|
Sign up to set email alerts
|

In vitrostudy of putative genomic biomarkers of nephrotoxicity through differential gene expression using gentamicin

Abstract: Drug-induced nephrotoxicity is one of the most frequently observed effects in long-term pharmacotherapy. The effects of nephrotoxicity are commonly discovered later due to a lack of sensitivity in in vivo methods. Therefore, researchers have tried to develop in vitro alternative methods for early identification of toxicity. In this study, LLC-PK1 cells were exposed to gentamicin through MTT and trypan blue assay. Concentrations of 4 (low), 8 (medium) and 12 (high) mM, were used to evaluate differential gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…The apparent permeability of the podocytes was evaluated at the end of the incubation time. The two concentrations were chosen in agreement with the literature [11][12][13] and after preliminary assays were done to evaluate the highest nontoxic dose for each compound in our podocyte model. Untreated and PAN-treated cells served as negative and positive control, respectively, for podocyte dysfunction.…”
Section: Modulation Of Podocyte Transport By Drugsmentioning
confidence: 99%
“…The apparent permeability of the podocytes was evaluated at the end of the incubation time. The two concentrations were chosen in agreement with the literature [11][12][13] and after preliminary assays were done to evaluate the highest nontoxic dose for each compound in our podocyte model. Untreated and PAN-treated cells served as negative and positive control, respectively, for podocyte dysfunction.…”
Section: Modulation Of Podocyte Transport By Drugsmentioning
confidence: 99%
“…Так, в исследовании, проведенном в США в 2017 г., было показано, что воздействие гентамицина вызывает повышение экспрессии четырех генов, кодирующих HAVcr1, ICAM-1, EXOC6 и каспазу-3. Сделан вывод о том, что эти гены играют важную роль в механизмах нефротоксичности, вызванной гентамицином, и могут быть использованы в качестве ранних биомаркеров нефротоксичности в исследованиях in vitro при разработке безопасных ЛП [84].…”
Section: использование биомаркеров нефротоксичности в исследованиях лекарственных препаратов In Vitrounclassified
“…Although KIM-1 is a sensitive and specific marker for kidney tubular injury, it is difficult to measure it in acute settings [53]. By contrast, Ichimura, et al [54] demonstrated that human KIM-1 exhibits homology to HAVCR1, and studies using gentamicin [55,56], amphotericin B [57], and cisplatin (no publishing data) have shown that the gene HAVCR1 (KIM1) might be used as in vitro biomarkers of nephrotoxicity.…”
Section: Biomarkers For Nephrotoxicitymentioning
confidence: 99%
“…Hence, it is paramount to use new tools in order to develop renal AOPs. Some studies have been performed utilizing biochemistry [154][155][156] and genomics [55][56][57]. However, it is important to make these data public through database, like the Comparative Toxicogenomics Database (CTD), in an attempt to achieve faster and more reliable results.…”
Section: Adverse Outcome Pathwaysmentioning
confidence: 99%